EFEKTIVITAS PENYELENGGARAAN TERTIB ADMINISTRASI KEPENDUDUKAN TERHADAP PENDUDUK NON PERMANEN DI KELURAHAN TONJA, DENPASAR - Ni Luh Putu Sri Utami; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Media Bina Ilmiah, 2025)
The phenomenon of high population mobility has given rise to a non-permanent population group that continues to grow and poses administrative challenges. The objective of this study is to analyze the effectiveness of the implementation of orderly population administration for non-permanent residents in Tonja Village, Denpasar, which is an area with high mobility due to tourism activities. The research method employed is qualitative descriptive, with data collection techniques including in-depth interviews and observations involving seven informants: four non-permanent residents, two village officials, and one population registration officer. The findings of the study suggest that the efficacy of population administration is suboptimal, attributable to three primary factors: the limited awareness among non-permanent residents regarding reporting procedures, the constraints in human resources and service infrastructure within the village, and the challenges in adapting to the utilization of information technology in population services. The findings of this study indicate that the implementation of population administration for non-permanent residents necessitates comprehensive enhancement, including the augmentation of public awareness, the training of officials, and the fortification of technology-based and participatory service systems.